Effects of bone marrow‐derived mesenchymal stromal cells on gene expression in human alveolar type II cells exposed to TNF‐α, IL‐1β, and IFN‐γ. Issue 16 (22nd August 2018) - Schwede, Matthew; Wilfong, Erin M.; Zemans, Rachel L.; Lee, Patty J.; dos Santos, Claudia; Fang, Xiaohui; Matthay, Michael A.
Abstract: The acute respiratory distress syndrome (ARDS) is common in critically ill patients and has a high mortality rate. Mesenchymal stromal cells (MSCs) have demonstrated therapeutic potential in animal models of ARDS, and their benefits occur in part through interactions with alveolar type II (ATII) cells. However, the effects that MSCs have on human ATII cells have not been well studied. Using previously published microarray data, we performed genome‐wide differential gene expression analyses of human ATII cells that were (1) unstimulated, (2) exposed to proinflammatory cytokines (CytoMix), or (3) exposed to proinflammatory cytokines plus MSCs. Findings were validated by qPCR. Alveolar type II cells differentially expressed hundreds of genes when exposed either to proinflammatory cytokines or to proinflammatory cytokines plus MSCs. Stimulation with proinflammatory cytokines increased expression of inflammatory genes and downregulated genes related to surfactant function and alveolar fluid clearance. Some of these changes, including expression of some cytokines and genes related to surfactant, were reversed by exposure to MSCs. In addition, MSCs induced upregulation of other potentially beneficial genes, such as those related to extracellular matrix remodeling. We confirmed several of these gene expression changes by qPCR. Thus, ATII cells downregulate genes associated with surfactant and alveolar fluid clearance when exposed to inflammatory cytokines, and mesenchymal stromal cells partially reverse many of these gene expression changes. Abstract : Mesenchymal stromal cells (MSCs) have therapeutic potential for the acute respiratory distress syndrome, and their benefits occur in part through interactions with alveolar type II (ATII) cells. We performed genome‐wide differential gene expression analyses of human ATII cells that were (1) unstimulated, (2) exposed to proinflammatory cytokines (CytoMix), or (3) exposed to CytoMix plus MSCs. Stimulation with CytoMix increased expression of inflammatory genes and downregulated genes related to surfactant function and alveolar fluid clearance, and several gene expression changes were reversed by exposure to MSCs.